TAFSIR MIMPI GENERASI Z MEMBACA RAMALAN MELALUI PLATFORM DIGITAL - Muhammad Abdul Aziz (NIHAYAH: Journal of Islamic Studies, 2025)
This study examines the phenomenon of dream interpretation among Generation Z, which has undergone a significant transformation in the digital era. With the widespread use of platforms such as TikTok, Instagram, and dream interpretation apps, young people are increasingly moving away from classical methods based on traditional Islamic texts and religious authorities. This research applies a qualitative approach through digital content analysis, a survey of 200 respondents aged 15–25, and case studies on five popular dream interpretation applications. The findings reveal that dream interpretation patterns are dominated by modern symbols such as social media, gadgets, and popular psychology. Approximately 68% of respondents prefer digital interpretations over consultations with religious scholars, and there is a rise in trends such as "instant interpretation" via chatbots or Google search. On the other hand, the prevalence of negative interpretations can trigger spiritual anxiety. These findings suggest that digital platforms are not only reshaping how Gen Z understands dreams but are also reconstructing religious experiences to be more personal and immediate, albeit with the risk of spiritual misinformation. This study recommends fostering digital literacy and developing credible Islamic content to address this phenomenon educationally.